2016
DOI: 10.1111/resp.12741
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of respiratory viral coinfections in children

Abstract: Respiratory infections are a common cause of paediatric morbidity. Clinical outcomes in children hospitalized with single respiratory virus infection are compared with those with two or more viral-viral coinfection. Studies were restricted to those reporting on children aged less than 5 years (PROSPERO CRD#42014009133). Published data to calculate risk ratios (RR) comparing children with single viral infections to coinfection using a random effects model were used. Similar analyses by pathogen pairs and by exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 31 publications
4
40
2
8
Order By: Relevance
“…The most common viruses detected in coinfections were RV/EV and RSV. Clinical importance of the viral coinfections is not clear as several studies detected no effect on the severity of the disease …”
Section: Discussionmentioning
confidence: 99%
“…The most common viruses detected in coinfections were RV/EV and RSV. Clinical importance of the viral coinfections is not clear as several studies detected no effect on the severity of the disease …”
Section: Discussionmentioning
confidence: 99%
“…3,10,32 The study of co-infection and the clinical features in children with RTIs were limited by the number of participants in this study. A previous study also demonstrated that neither viral load nor viral co-infections were significantly associated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of ALRI is viral infection and there remains doubt as to whether co-infections with more than one virus increase the severity of infection. Lim et al 83 performed a systematic review and meta-analysis of respiratory co-infections in children and found no evidence of increased clinical severity of co-infections, although point estimates did suggest the possibility of increased risk of admission to intensive care and further careful studies will be needed to better understand these risks. In addition to clinical factors and variable pathogen factors, we also recognize that healthcare practices and behaviours vary considerably and may influence admission to hospital, use of intensive care, length of stay etc.…”
Section: Claire E Wainwrightmentioning
confidence: 99%